ANALISIS POSTUR TUBUH PEKERJA MESIN PEMBELAH KAYU DI INDUSTRI MEBEL SUPRI MENGGUNAKAN METODE RULA - Aris Fiatno (Research Center University of Pahlawan Tuanku Tambusai, 2019)
The Supri furniture industry is an industry that processes raw materials or semi-finished materials into finished products. The furniture industry is one of the growing industrial sectors in Indonesia, as an industry engaged in furniture or furniture, there are several machines used to support productivity. Early observation research methodology in the form of evaluating the potential and symptoms of musculoskeletal complaints with the help of a nordic body map questionnaire, analysis using the RULA method approach, Preliminary observations in the form of subjects observed in this study were 3 male wood splitting workers with an average age of 42 years and had worked for 3 years. The waist, back, neck, eyes and arms are the areas that many workers complain about. The resulting wood dust can make the eyes sore. Sometimes workers suffer from cough despite having used a mask. From the above table it can also be seen that workers with a height of 175 cm experience lower back, neck and neck pain more seriously than other workers. o that work is not too risky, equipment and workplaces should be designed according to worker anthropometry.